THE RUSSIAN LANGUAGE: HISTORY, CIVILIZATION, CULTURE - Kondakov, B.V.; Nazmutdinova, S.S.; Chugaeva, T.N.; Kavardakova, E.L.; Popov, D.S.; Chugaev, N.V.; Shpak, N.E. (Perm Federal Research Centre Journal, 2015)
The article looks into the issues of the Russian language and literature as an expression of the national spirit. Problems of Russian as a native and foreign language, its place in the world are considered. The status of Russian as a world language and lingua franca is discussed. The historical way of the Russian language is traced. Contributions of outstanding personalities of Russia and Perm Krai in the development of culture are estimated. Urgent problems of the Russian language and its culture are discussed. Practical assignments on correctness of Russian and some testing materials on Russian literature and poetry are offered.